Original paperMetformin is not associated with improved biochemical free survival or cause-specific survival in men with prostate cancer treated with permanent interstitial brachytherapy - Taira, Al V.; Merrick, Gregory S.; Galbreath, Robert W.; Morris, Mallory; Butler, Wayne M.; Adamovich, Edward (Journal of Contemporary Brachytherapy, 2014)
Purpose: Several recent studies have suggested improved clinical outcomes in diabetic men with prostate cancer who also use metformin. We explore whether metformin use is associated with improved outcomes specifically in men undergoing prostate brachytherapy. Material and methods: 2,298 consecutive patients underwent permanent interstitial brachytherapy by a single brachytherapist (GSM). The cohort included 2028 non-diabetic men, 144 men with diabetes who were not taking metformin, and 126 men with diabetes who were taking metformin. Median follow up was 8.3 years. Differences in biochemical free survival, cause specific survival, and overall survival between men taking metformin and those not taking metformin were compared using Kaplan-Meier curves and log rank tests. Results: Fifteen year biochemical failure rate, cause specific mortality and overall mortality for non-diabetic men was 4.6%, 1.5%, 47.0%, respectively; for diabetic men taking metformin 4.8%, 2.0%, 37.2%; and for diabetic men not taking metformin was 2.8%, 0%, 72.7%, respectively. Metformin use was not predictive in multivariate analysis of biochemical failure or prostate cancer specific mortality. However, diabetic men not taking metformin had higher overall mortality than non-diabetic men. Conclusions : Metformin use was not associated with improved biochemical survival or cancer specific survival in this cohort of men treated with prostate brachytherapy.